2020
DOI: 10.1177/2042753020936785
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mobile games in the context of content: What do children face when playing mobile games?

Abstract: The aim of this study is to examine mobile games in the context of their content and to evaluate the situations faced by children through document analysis in terms of age-rating, game score, access permissions, the inclusion of advertisements, in-game purchases, encouraging consumerism, the inclusion of violence, bad habits, and educational value. The review and rating data of the games which can be found in Common Sense Media and Google Play Store were included in the study. These data were analyzed by descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…It finds its application in the video chatting apps which include storytelling and uttering vocabulary as the game proceeds into the next stage. There are several science and mathematics based games which foster skill development and problem solving abilities in the children (Göksu et al, 2020). The interactive mobile games designed today for children converge to the idea that it needs to be entertaining along with providing some sort of benefit to their developmental state of mind (Anthony et al, 2021;Gocheva et al, 2020).…”
Section: Review Of Literature Entertainment Value Of Mobile Games For...mentioning
confidence: 99%
“…It finds its application in the video chatting apps which include storytelling and uttering vocabulary as the game proceeds into the next stage. There are several science and mathematics based games which foster skill development and problem solving abilities in the children (Göksu et al, 2020). The interactive mobile games designed today for children converge to the idea that it needs to be entertaining along with providing some sort of benefit to their developmental state of mind (Anthony et al, 2021;Gocheva et al, 2020).…”
Section: Review Of Literature Entertainment Value Of Mobile Games For...mentioning
confidence: 99%
“…Thus, an app that breaks children's privacy protection laws can still be rated as "appropriate" for children aged 4 years and over. While academic research on the effectiveness of platform-based rating systems is still emerging, a growing number of studies indicate such trends are dominant (Göksu, Aslan, & Turgut, 2020;Reyes et al, 2018;Radesky, Schumacher, & Zuckerman, 2015). Government of Canada must now ensure that "all duty bearers within their jurisdiction meet their responsibilities to children's rights -including businesses and others whose activities significantly impact on children" (Livingstone, 2021).…”
Section: Canadian Game Regulation and The Esrbmentioning
confidence: 99%
“…Several studies were found to have investigated student emotions (Chen & Husnaini, 2020;Göksu, Aslan, & Turgut, 2020;Kenny, Lyons, & Lynn, 2017;Lee, 2019;B. Lee, Jeon, Jang, & Yoo, 2018;Metzger & Paxton, 2016), attitudes and perceptions (Djundubaev, 2017;Gulinna & Lee, 2020;J.…”
Section: Cluster Identificationmentioning
confidence: 99%